Strategi Kepala Madrasah dalam Pengembangan Kompetensi Profesional Guru di Madrasah Tsanawiyah Raudhatul Mujawwidin Rimbo Bujang Tebo Jambi - Suyatno Suyatno (Dinasti Review, 2022)
Abstract: This study aimed to determine the steps, constraints, and results of the principal's strategy in developing the professional competence of teachers at Madrasah Tsanawiyah Raudhatul Mujawwidin Rimbo Bujang Tebo Jambi. This type of research is field research through a qualitative approach with descriptive methods. The strategic steps the head of the madrasa implements are formal and non-formal strategies. The formal strategy includes teachers in IHT activities, courses, training, MGMPs, seminars, and the head of the madrasa supervises the teachers. Non-formal strategies encourage teachers to develop their competencies independently by going online, discussing, motivating, and applying discipline. The inhibiting factors are lack of literacy, lack of creativity, lack of information technology use, and minimal teacher research. The development model used is implementing In-House Training (IHT). The impact or results of the strategies implemented by the head of the madrasa in this study indicate that teachers in carrying out their duties and responsibilities are increasing professionally, the discipline of madrasa residents is increasing, and teachers are motivated in educating students, and students are increasingly enthusiastic in learning so that their achievements also increase. Abstrak: Penelitian ini bertujuan untuk mengetahui langkah, kendala, dan hasil strategi kepala sekolah dalam mengembangkan kompetensi profesional guru di Madrasah Tsanawiyah Raudhatul Mujawwidin Rimbo Bujang Tebo Jambi. Jenis penelitian ini adalah penelitian lapangan melalui pendekatan kualitatif dengan metode deskriptif. Langkah strategis yang dilakukan kepala madrasah adalah strategi formal dan nonformal. Strategi formal meliputi guru dalam kegiatan IHT, kursus, pelatihan, MGMP, seminar, dan kepala madrasah mengawasi guru. Strategi nonformal mendorong guru untuk mengembangkan kompetensinya secara mandiri dengan cara daring, berdiskusi, memotivasi, dan menerapkan disiplin. Faktor penghambatnya adalah kurangnya literasi, kurangnya kreativitas, kurangnya pemanfaatan teknologi informasi, dan minimnya riset guru. Model pengembangan yang digunakan adalah menerapkan In-House Training (IHT). Dampak atau hasil dari strategi yang diterapkan kepala madrasah dalam penelitian ini menunjukkan bahwa guru dalam menjalankan tugas dan tanggung jawabnya semakin meningkat secara profesional, kedisiplinan warga madrasah semakin meningkat, dan guru termotivasi dalam mendidik siswa, serta siswa semakin semangat dalam belajar sehingga prestasinya juga meningkat.